Filsafat Manajemen Pendidikan Islam Dalam Perspektif Rekonstruktivisme - Alamsyah, Muhammad Baha'ul (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Abstract Reconstructivism emphasizes renewal and transformation in Islamic education to face changing times. This approach includes criticism of tradition, contextualization of Islamic education in social and cultural realities, encouragement of innovation and transformation, openness to pluralist thinking, and development of student independence and criticality. The method used in this article is a library research. The results show that through the reconstructivism approach is expected to increase its relevance and effectiveness in accordance with Islamic values in the context of changing times.